PENGARUH MEDIA PENDINGIN TERHADAP KEKERASAN BAJA KARBON: STUDI EKSPERIMENTAL PADA VARIASI QUENCHING MEDIA - Andrianto, Sis Nanda Kus; Andromeda, Tata; Sasongko, Muhammad Ilman Nur; Yazirin, Cepi (Journal of Industrial Engineering & Technology Innovation, 2025)
This research analyzes the effect of cooling media types on the hardness of carbon steel through the quenching process using water, oil, and air. Variations of cooling media are selected based on differences in cooling rates that theoretically affect the transformation of microstructures, especially the formation of martensite. The research method is experimental by heating carbon steel to 850 °C, followed by quenching on three different media. The Rockwell C hardness test shows a significant difference between the three media. Water-cooled samples have the highest hardness value, followed by oil, while air cooling produces the lowest hardness. This result is in line with the cooling rate theory and phase transformation kinetics (TTT/CCT diagram). Research findings contribute to the optimization of the heat treatment process in the manufacturing industry to choose a cooling medium that is suitable for the strength and toughness of the components.